Incidence of influenza and other respiratory viruses among pregnant women: A multi‐country, multiyear cohort. Issue 2 (11th December 2021) - Azziz‐Baumgartner, Eduardo; Veguilla, Vic; Calvo, Arlene; Franco, Danilo; Dominguez, Rhina; Rauda, Rafael; Armero, Julio; Hall, Aron J.; Pascale, Juan M.; González, Rosalba
Abstract: Objective: To quantify rates of influenza illness and assess value of influenza vaccination among pregnant women in Panama and El Salvador. Methods: Pregnant women were enrolled and followed each week in a prospective cohort study to identify acute respiratory illnesses (ARI). Nasopharyngeal swabs obtained from women with febrile ARI were tested by reverse‐transcription polymerase chain reaction for influenza and other respiratory viruses. Results: We enrolled 2556 women between October 2014 and April 2017. Sixteen percent developed at least one ARI; 59 had two ARI, and five had three ARI for a total of 463 ARI. Women in El Salvador and Panama contributed 297 person‐years (py) and 293 py, respectively, during influenza circulation. Twenty‐one (11%) of 196 sampled women tested positive for influenza. Influenza incidence was 5.0/100 py (5.7/100 py in El Salvador and 4.3/100 py in Panama). Only 13% of women in El Salvador and 43% in Panama had been vaccinated against influenza before influenza epidemics ( P < 0.0001). Conclusions: One in six pregnant women developed ARI and more than one in ten ARI were attributable to vaccine‐preventable influenza. While women were at risk of influenza, few had been vaccinated before each epidemic. Such findings suggest the utility of evaluations to optimize vaccine timing and coverage. Abstract : One in six pregnant women developed ARI and ≥10% were attributable to vaccine‐preventable influenza. Few pregnant women, however, were vaccinated against influenza before each epidemic.